Systematic review and meta-analysis of the intervention effect of curcumin on rodent models of myocardial infarction - Pang, Bing-Yao; Wang, Ya-Hong; Ji, Xing-Wang; Leng, Yan; Deng, Hou-Bo; Jiang, Li-Hong (Frontiers in Pharmacology, 2022)
Objective: This study aimed to evaluate the intervention effect of curcumin in myocardial infarction rodent models. Methods: A systematic retrieval of relevant studies on curcumin intervention in rats or mice myocardial infarction models was conducted, and the data were extracted. The outcome indicators included biochemical blood indicators, such as creatine kinase (CK), creatine kinase isoenzyme (CK-MB), malondialdehyde (MDA), lactate dehydrogenase (LDH) and superoxide dismutase (SOD), as well as cardiac tissue structure indicators, such as left ventricular weight to body weight ratio (LVW/BW), apoptosis index, left ventricular end-diastolic dimension (LVEDD), left ventricular end-systolic diameter (LVESD), and myocardial infarction area, and hemodynamic indexes, such as systolic blood pressure (SBP), diastolic blood pressure (DBP), left ventricular end-diastolic pressure (LVEDP), left ventricular ejection fraction (LVEF), left ventricular fractional shortening (LVFS), maximum rate of left ventricular pressure rise (+dp/dtmax), and maximum rate of left ventricular pressure decline (–dp/dtmax). These results were then analyzed by meta-analysis. Studies were evaluated for methodological quality using the syrcle’s bias risk tool. Results: A total of 24 studies were included in the meta-analysis. The quality assessment of included studies revealed that the evidence was low quality and none of studies was judged as having a low risk of bias across all domains. The results revealed that curcumin could reduce CK-MB, CK, LDH, and MDA levels. They also revealed that it could lower SBP, DBP, LVEDP, LVW/BW, apoptosis index, LVEDD, LVESD, and myocardial infarction area and increase LVEF, LVFS, +dp/dtmax, and–dp/dtmax. However, it had no significant impact on the heart rate and the levels of SOD in the models. Conclusion: Curcumin alleviates myocardial injury and oxidative stress in myocardial infarction rodent models in terms of blood biochemistry indicators, improves the diastolic and systolic capacity of the ventricle in terms of hemodynamic indexes, and reduces the necrosis and apoptosis of cardiomyocytes in terms of tissue structure. The methodological quality of the studies was low and additional research is warranted.